PERAN AJARAN SEKSUALITAS KLASIK DALAM TEKS LONTAR RSI SEMBINA BAGI PERKEMBANGAN PENDIDIKAN KESEHATAN REPRODUKSI: THE ROLE OF CLASSICAL SEXUALITY TEACHING IN THE TEXT OF LONTAR SEMBINA RSI FOR DEVELOPMENT OF REPRODUCTIVE HEALTH EDUCATION - Widana, Anak Agung Gde Oka; Subhaktiyasa, Putu Gede (Stikes Wira Medika Bali, 2019)
The main problems studied in this research are the structure of the text, the teachings of classical sexuality contained in the Lontar Rsi Sembina text and the role of the teachings of classical sexuality in the text of Rsi Sembina for the development of reproductive health education. This type of research is qualitative research with a psychological approach. Data obtained was collected using library techniques and recorded documents. The collected data is then analyzed by qualitative and hermeneutic descriptive techniques. The results of this study indicate that the composition of the content is structured in the form of formal structures (manggala, corpus, epilogue, language) and narrative structures (themes and speech aspects). The teachings of classical sexuality contained therein are centered on four main things, namely the Teachings of Harmony, the Teachings of Sanggama Yoga, the Teachings of Spiritual Healing, and the Teachings of Usada. The role of the teachings of classical sexuality in the text of Rsi Sembina is for the development of reproductive health education, including; The Role of Ethics or Decency, Educational Roles, The Role of Non-Verbal Communication or Body Language, and Alternative Roles.